Developing and validating the ACCA (Activation-Collaboration-Creation-Application) learning model to enhance students’ collaboration - Andi Muharni; Susriyati Mahanal; Siti Zubaidah; Hendra Susanto; H. Hardianto (Universitas Muhammadiyah Malang, 2025)
Collaboration skills are crucial for students to engage in teamwork, solve problems collectively, and construct deeper understanding through interactive discussions. However, existing research indicates that these skills remain underdeveloped, primarily due to lecturer-centered teaching approaches and limited social interaction—particularly in subjects like animal physiology. This study aims to develop and validate the ACCA (Activation–Collaboration–Creation–Application) learning model as a valid, practical, and effective framework for enhancing student collaboration. Employing a Research and Development (R&D) methodology based on the Plomp and Nieveen (2013) model, the study proceeded through three phases: Preliminary Research, Prototyping, and Assessment. The model was validated by experts, tested for practicality, and evaluated for effectiveness through classroom implementation. The results indicate that the ACCA model meets the criteria for validity, practicality, and effectiveness in improving students’ collaborative competence. It significantly fosters active engagement, mutual problem-solving, and shared knowledge construction. The ACCA model offers an innovative and adaptable instructional strategy applicable across various disciplines by promoting a more interactive and structured learning environment.